PUBLIC RELATIONS STRATEGY IN REALISING VISION, MISSION AND SCHOOL IMAGE - Nilla Putri Salsabila; Narendra Jumadil Haikal Ramadhan; Azis Gaffar; Muhammad Amin Nur (Esteem Journal of English Education Study Programme, 2025)
This study aims to determine the strategies used by public relations in realising vision and mission and school image at DDI Mangkoso Junior High School. This research is qualitative research with a case study approach. The primary data source in this study is the Vice Principal for Public Relations. The technique used for data analysis is a direct observation in the field. The results of this study indicate that the public relations strategy in realising vision and mission and school image at DDI Mangkoso Junior High School through several effective steps, namely 1) empowering alumni, 2) delegating competitions, 3) social media content and 4) interactive communication with student guardians. The impact of the public relations strategy in realising vision and mission and school image is the significant increase in the number of new student registrants at DDI Mangkoso Junior High School in the last five years. Through the strategy and its impact, it can be seen that the existence of public relations in the school has a very important role in realizing the vision and mission and school image. This research not only contributes theoretically, but also provides an overview of how to plan and implement effective school communication strategies.